PROPRIEDADES MECÂNICAS E MICROESTRUTURAIS DE PORCELANATOS SUBMETIDOS A DIFERENTES TEMPOS DE SINTERIZAÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
The knowledge of the microstructures and final properties of ceramic masses allow to determine the advantages and limitations of its application in specific conditions. This work had for objective to study the microstructural development of a known mass of porcelainized stoneware formulated with raw materials from south Brazil, especially the formation of the phase mulita, and its influence on the mechanical properties. For so many different amounts of kaolin were added (it already leaves constituent of the mass), to obtain a variation of the amount of phase mulita, and each obtained composition was sintering in 4 different times (30, 60, 120, 240 minutes), being compared the mechanical properties and microstructures obtained in each case. It was verified that as larger the burning time, larger the resistance of the stoneware ceramic. With the kaolin addition the resistance increases to certain point, producing inverse effect for larger amounts than 24% in the ceramic mass in the temperatures of sintering from 120 to 240 minutes. The largest resistance value was 67,54 MPa, obtained in the composition with addition of 24% of kaolin and sintered for 240 minutes. It was observed that the porosity and the absorption of the samples decrease significantly with the increase of the kaolin contents and increase of the temperature. The compositions were analyzed by X ray diffractometry, Scanning Electronic Microscopy, rupture module and physical characterization of samples.
MECHANICAL PROPERTIES AND MICROESTRUCTURES OF STONEWARE CERAMICS SUBMITTED TO DIFFERENT CONDITIONS OF SINTERING
Keywords: Mulita; microestrutura; grês porcelanato; propriedade mecânica; Mulita; microstructure; stoneware ceramics; mechanical property; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA